Efficient and provably secure certificateless multi-receiver signcryption - Selvi S.S.D.; Vivek S.S.; Shukla D.; Rangan Chandrasekaran P. (My University, 2025)
Certificateless cryptography aims at combining the advantages of identity based and public key cryptography, so as to avoid the key escrow problem inherent in the identity based system and cumbersome certificate management in public key infrastructure. Signcryption achieves confidentiality and authentication simultaneously in an efficient manner. Multi-receiver signcryption demands signcrypting the same message efficiently for a large number of receivers. In this paper, we propose the first efficient certificateless multi-receiver signcryption scheme and prove it secure in the random oracle model. Our scheme does not require pairing to signcrypt a message for any number of receivers. We are considering a more realistic adversarial model and proving the security against insider attacks, which guarantees non-repudiation and forward secrecy. © 2008 Springer Berlin Heidelberg.